Character Education Analysis in The Natural Sciences Textbook of 9th Grade (Student Book): a Case of Chemistry Subject - Permatasari, Anggraeni Dian; Hadiana, Deni (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2024)
Education is not only to develop cognitive aspects but also to develop the character of a human being. As one of the primary learning sources, the textbook also has to accommodate character education. This study aimed to analyze character education in chemistry subject in the natural sciences textbook of 9th Grade, especially student book. The textbook that was analyzed was published by the Ministry of Education, Culture, Research, and Technology. The study was conducted by a qualitative method using the content analysis technique. Two chapters are analyzed. Particles Composing Objects and Living Things and Eco-friendly Technologies. The study revealed that these two chapters contained all values of Basic Competencies 3 and 4 in Curriculum 2013 (religious, care, responsibility, discipline, honesty, confidence, communicative, creative, scientific thinking, curiosity, democratic, and collaboration).